Cover cropping in rainfed olive orchards - Rodrigues, M.A. (2017)
Cover cropping has been advocated as a mean of reducing soil erosion and increasing soil organic matter and functional biodiversity. There are many other good reasons to establish a cover crop in an orchard since it can improve in several ways the physical, chemical and biological properties of a soil. However, herbaceous vegetation competes for resources. In intensivemanaged orchards, without limitation of available water and nutrients, probably this is a minor problem. In rainfed orchards, to balance the potential beneficial effects of cover crops and their strong competition for resources in particular for available water is a great challenge. In this work, we report results from field trials from which we are proposing a model of intervention in rainfed managed orchards consisting of the use of very early maturing self-reseeding annual legumes as a cover crop. These plants are able to enrich the soil with nitrogen and to protect the soil all year round through a green cover of vegetation during autumn-spring and a mulch of dead material during summer. Experimental results also showed that nitrogen nutritional status of the olive trees and olive yields increased in comparison to a plot of natural vegetation fertilized with 60 kg N ha-1 yr-1.